Geomagnetic investigation of mineral rocks at Awo, Osun state, southwest Nigeria - Ojo, Akintayo Olufemi; Popoola, O. I. (International Journal of Advanced Geosciences, 2014)
A ground magnetic study was carried out to identify the locations and depths of formation of different magnetic minerals at Awo town, Egbedore local government area of Osun State, Southwest Nigeria. On the study area, ten magnetic traverses were occupied with 10m spacing in between each traverses and 10m station intervals. The traverses were 100m long orientated in East - West direction. After correcting the magnetic data for the effect of drift and regional magnetic variation of the study area, the calculated magnetic anomalies were used in plotting the 3D view maps, and carrying out forward and inverse calculations (3D inversion) of the subsurface of the study area using MAG3D inversion program. The interpretation of each profile (traverses) and 3D inversion shows variable anomaly, which is indicative of contrast in the susceptibility of the subsurface. The results possibly suggest that mineral rocks with high magnetic susceptibility values (between 7.15 and 4.72) such as Columbite and Tantalite were buried from the centre towards the south western region of the study area at depth between 20m and 90m; while mineral rocks with low magnetic susceptibility values (between – 7.40 and – 5.00) such as Sandstone, Quartz and Calcite were harboured at the north western region at depth between 75m and 100m. More than fifty percentage of the volume has an intermediate magnetic susceptibility values (between – 4.00 and 4.00) indicating that the region is predominantly a schist pegmatite vein that probably contains mineral deposits such as Beryl, Tourmaline and Mica in both disseminated and massive quantities.   Keywords: Awo town, magnetic minerals, magnetic susceptibility, 3d views maps, 3d inversion.